2016
DOI: 10.1371/journal.pone.0168860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propidium Monoazide (PMA) Treatment on Mycobiome and Bacteriome Analysis of Cystic Fibrosis Airways during Exacerbation

Abstract: Introduction and PurposePropidium monoazide (PMA)-pretreatment has increasingly been applied to remove the bias from dead or damaged cell artefacts, which could impact the microbiota analysis by high-throughput sequencing. Our study aimed to determine whether a PMA-pretreatment coupled with high-throughput sequencing analysis provides a different picture of the airway mycobiome and bacteriome.Results and DiscussionWe compared deep-sequencing data of mycobiota and microbiota of 15 sputum samples from 5 cystic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…mRNA undergoes rapid metabolism by intracellular and extracellular RNase 15 and has an overall lifetime of only a few minutes to hours. 26,27 The aims of our study were: to investigate the existence of viable organisms in the lymph nodes of subjects with and without IBD using molecular techniques and to compare the bacteria present in the lymph nodes with the same patient's gut microbiome. 17 While 16S rRNA is generally stable, degradation occurs under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA undergoes rapid metabolism by intracellular and extracellular RNase 15 and has an overall lifetime of only a few minutes to hours. 26,27 The aims of our study were: to investigate the existence of viable organisms in the lymph nodes of subjects with and without IBD using molecular techniques and to compare the bacteria present in the lymph nodes with the same patient's gut microbiome. 17 While 16S rRNA is generally stable, degradation occurs under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, as this has been associated with a moderate false positive rate, 25 RNA detection is preferred in tissues with low bacterial abundances. 26,27 The aims of our study were: to investigate the existence of viable organisms in the lymph nodes of subjects with and without IBD using molecular techniques and to compare the bacteria present in the lymph nodes with the same patient's gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…One obvious inconsistency is the use of propidium monoazide (PMA), a chemical compound that binds DNA in cells with damaged membranes and hence allows exclusion of non-viable DNA from sequencing. Excluding non-viable DNA has been suggested to be important for accurately identifying which members of the community are active at times of exacerbation and helps to avoid overestimation of viable microorganisms following treatment with antibiotics, but it is not utilised by all groups [51,52]. There are concerns that PMA may incompletely penetrate sputum, hence only identifying a portion of non-viable cells.…”
Section: Community Changes Associated With Treatment For Acute Pulmonmentioning
confidence: 99%
“…Therefore, it is vital that such analyses choose an appropriate and consistent DNA extraction method which will provide efficient extraction from all cell types and comparable extraction efficiency from different sample types. Nyugen et al performed 16S and internal transcribed spacer (ITS) sequencing and identified Candida as the most predominant fungal genera in CF sputum samples [67]. However, the enzyme-based DNA extraction protocol they used may have favoured the extraction of yeast compared to fungi.…”
Section: Limiting Factors Of Sample Processing In Mycobiome Studiesmentioning
confidence: 99%
“…A high person-to-person variation in mycobiome composition has been reported. Few studies to date have analysed samples in replicates and most only include technical replicates at the PCR stage [37,67]. Bittinger et al [20] performed repeat extractions from samples and found poor reproducibility between replicates, with instances of high abundance of an operational taxonomic unit (OTU) in one replicate and absence in another.…”
Section: Reproducibility In Mycobiome Researchmentioning
confidence: 99%